2019
DOI: 10.7759/cureus.5959
|View full text |Cite
|
Sign up to set email alerts
|

Is Stem Cell Therapy an Answer to Heart Failure: A Literature Search

Abstract: The heart is one of the most industrious organs in the human body. It starts beating in the first few weeks of embryonic life and keeps pumping blood till death. This organ can host a range of diseases as well. Some can hamper the vasculature, while others can affect its electrical activity, the heart valves, etc. All these conditions can lead to end-stage failure where it can no longer meet the requirements of the body's milieu. This imbalance between supply and demand leads to an array of symptoms. Medical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…These therapies, which involve growing vast numbers of cells in vitro (potentially more than the 1 billion CMs that may be lost following MI) and injecting them directly into the injured heart, have shown promise in numerous pre-clinical settings. However, results for this relatively new strategy are often inconsistent and fail to achieve marked improvements in cardiac function (reviewed by Müller et al 2018 ; Tehzeeb et al 2019 ), and studies in animal models have revealed concerning and prevalent side effects including arrhythmias and tachycardia (Shiba et al 2016 ; Liu et al 2018 ; and reviewed by Chen et al 2020 ). These inconsistencies may be partly explained by a recent and important publication from Vagnozzi et al ( 2020 ) which has found that direct chemical stimulation of the innate immune system produces an outcome comparable to treatment with cell therapies previously reported to be reparative in models of cardiac ischaemic injury (Vagnozzi et al 2020 ).…”
Section: Current Therapeutic Outlookmentioning
confidence: 99%
“…These therapies, which involve growing vast numbers of cells in vitro (potentially more than the 1 billion CMs that may be lost following MI) and injecting them directly into the injured heart, have shown promise in numerous pre-clinical settings. However, results for this relatively new strategy are often inconsistent and fail to achieve marked improvements in cardiac function (reviewed by Müller et al 2018 ; Tehzeeb et al 2019 ), and studies in animal models have revealed concerning and prevalent side effects including arrhythmias and tachycardia (Shiba et al 2016 ; Liu et al 2018 ; and reviewed by Chen et al 2020 ). These inconsistencies may be partly explained by a recent and important publication from Vagnozzi et al ( 2020 ) which has found that direct chemical stimulation of the innate immune system produces an outcome comparable to treatment with cell therapies previously reported to be reparative in models of cardiac ischaemic injury (Vagnozzi et al 2020 ).…”
Section: Current Therapeutic Outlookmentioning
confidence: 99%
“…Heart Tissue: Structure, Cells Types, Cell Ratio, 3D Models Developmentally, the heart is the first organ to form in the embryo and it plays a vital role in supplying oxygen and nutrients to the body [8,12]. It is composed of four chambers: two atria, which collect the non-oxygenated blood, and two ventricles, which pump oxygenated blood to all organs and tissues [12,22].…”
Section: Cardiovascular Microenvironment or Nichementioning
confidence: 99%
“…A heart transplant is the gold-standard treatment for heart failure patients [7,8]. Although the majority of heart transplant patients survive for years, the procedure comes with major risks for the patient, including transplant rejection and other complications, such as vasculopathies, dysfunctions, and infections [7][8][9]. Another issue linked to heart transplantation is the lack of availability of donor hearts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that need to be investigated and have been undergoing research are the type of stem cells used, application of the stem cells, dose, concentration, timing, patient 1 2 population, and adverse outcomes. Safety concerns with regard to stem cell therapy in the myocardium are most related to increased incidence of ventricular arrhythmias [5]. While there has been much anticipation for the application of stem cells, research has so far been mixed.…”
Section: Introductionmentioning
confidence: 99%